PSYCHO library for Pure Data - Porres, Alexandre (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
This paper describes the PSYCHO library for the Pure Data programming language. This library provides novel functions for Pure Data and is a collection of compiled objects, abstractions and patches that include psychoacoustic models and conversions. Most notably, it provides models related to Sensory Dissonance, such as Sharpness, Roughness, Tonalness and Pitch Commonality. This library is an evolution and revision of earlier research work developed during a masters and PhD program. The previous developments had not been made easily available as a single and well documented library. Moreover, the work went through a major overhaul, got rid of the dependance of Pd Extended (now an abandoned and unsupported software) and provides new features. This paper describes the evolution of the early work into the PSYCHO library and presents its main objects, functions and contributions.